Turning away - Matthews, A (Maney Publishing, 2010)
This article provides a comparative analysis of the treatment of space in the German life of Dorothea and in the related Latin life. Moving beyond the tendency of previous research to concentrate on the contextual differences between Latin and vernacular and on the theme of enclosure in female spirituality, it examines the motion of the turning character in both texts, showing how they link Dorothea’s presence in space to her relationship with God and with other human beings. In particular, the article focuses on how Dorothea turns away from the world and seeks out corners where she can be alone, with God, how she then withdraws from the world in her cell, and how she is finally isolated in death. The texts discussed show that the space inhabited by this particular female mystic is more complex than can be accounted for in readings that operate solely in terms of the enclosure of the gendered body.